(untitled) (Journal of Psychiatrists’ Association of Nepal, 2018)
Introduction: Prisoners are one of the most vulnerable groups for having high prevalence of mental illness. There is a dearth of major studies conducted amongst prisoners in Nepal. The basic objective of this study is to study prevalence and nature of psychiatric morbidity in prisoners attending general OPD of Central jail Hospital, Kathmandu. Material and Method: This was a descriptive, cross-sectional study carried out in prisoners attending OPD of central jail for a period of six months. Initial screening was done with self- reporting questionnaire (SRQ) and those having distress on SRQ were interviewed and diagnosis was made based on ICD-10 DCR and data analysis was done using SPSS version 16. Results: A total of 121 prisoners out of 300 prisoners attending OPD of central jail hospital during a period of six months had been diagnosed to suffer from psychiatric morbidity. Majority of cases were within age group 26-30 years (20.7%) with male preponderance (76.9%), married (69.4%), educated up to higher secondary level (38%), doing occupation as labor work (24%), Hindus (62.8%) with janajatis (32.2%), having low socioeconomic status (51.2%), belonging to joint family (50.4%) and were from rural areas (45.4%). Murder was the most common offence committed (33.9%) followed by drug trafficking (28.1%). Most common primary diagnosis belong to Neurotic, stress related and somatoform disorder (57%) followed by mood disorder (32.2%). Most common psychiatric morbidity among prisoners was generalized anxiety disorder (36.4%) followed by Moderate depressive episode (23.1%) and somatoform disorder (9.1%). The overall prevalence of psychiatric morbidity in prisoners attending OPD of central jail hospital was found to be 40.33%. Conclusion: A substantial burden of psychiatric morbidity exists in prison population of Nepal. Prompt recognition and treatment of mental illness in prison lead to decrease in functional disability and better quality of life.